2005
DOI: 10.1074/jbc.m411672200
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Monochloramine Activates a Cell Death Pathway Involving Bax and Caspase-9

Abstract: Taurine is an abundant free amino acid that interacts with the potent oxidant hypochlorous acid to form the less toxic and more stable oxidant taurine monochloramine (TauNHCl). TauNHCl has diverse cellular effects ranging from inhibiting the production of proinflammatory mediators to inhibiting cell proliferation and inducing cell death. We hypothesized that TauNHCl could activate a cell death pathway involving Bcl-2 members and the activation of caspase proteases. FL5.12 cells are lymphocytic cells that under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…A recent study by Emerson et al has shown that NCT dosedependently inhibits inflammatory cytokine release and can induce cell death in the murine hematopoietic prolymphocytic B cell line FL5.12 via mitochondrial damage inducing the classic mitochondrial apoptosis pathway. 11 Previously NCT has been shown to mediate apoptosis in the Burkitt's lymphoma cell lines JLP-119 10 and BL-41. 17 The remarkable tolerability of NCT has been shown in various in vitro and in vivo studies, including animal models and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study by Emerson et al has shown that NCT dosedependently inhibits inflammatory cytokine release and can induce cell death in the murine hematopoietic prolymphocytic B cell line FL5.12 via mitochondrial damage inducing the classic mitochondrial apoptosis pathway. 11 Previously NCT has been shown to mediate apoptosis in the Burkitt's lymphoma cell lines JLP-119 10 and BL-41. 17 The remarkable tolerability of NCT has been shown in various in vitro and in vivo studies, including animal models and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Omnivores ingest a mean daily amount of 58 mg taurine, which occurs naturally in food, especially meat and seafood. 12 It plays an important role in several essential biological processes, such as development of the central nervous system and retina, calcium modulation, membrane stabilization, reproduction, and immunity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Myeloperoxidase deficiency suppresses also PMN apoptosis (Tsurubuchi et al, 2001;Milla et al, 2004). Several myeloperoxidase products such as hypothiocyanite, monochloramine and taurine chloramine are potent inducers of apoptosis (Emerson et al, 2005;Lloyd et al, 2008;Ogino et al, 2009). …”
Section: Generation Of Oxidants During Pmn Apoptosismentioning
confidence: 99%